- Profile of Ecoliteracy Ability of Science Students On Environmental Issues: Ecoliteracy Ability - Taufik, Annisa Novianti; Berlian, Liska; Wahyuni, Ajeng Restu; Khofifah, Mia (UNIB Press, 2024)
This study aims to provide an overview of the profile of students ecoliteracy skills in the context of environmental issues such as waste, forest destruction, and climate change. This type of research is descriptive qualitative to obtain information related to the level of ecoliteracy skills of fourth semester students. The sampling technique used random sampling with a total of 27 science students in batch 2022. The research instrument used is a self assessment that adapts to the assessment indicators of maintaining environmental sustainability, using energy properly and utilizing existing resources with ecological principles. The result showed that the level of ecoliteracy skills of students obtained an average percentage of 71% and was in the good category. This finding shows that most student have an understanding of ecoliteracy and are able to practice it well through actions that are oriented towards sustainability values.